Equations of Prices, Wages and Financial Flows in W8D-2010 - Gosińska, Emilia; Leszkiewicz-Kędzior, Katarzyna; Welfe, Władysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article defines a system of price equations, the producer prices being its core. It is assumed that they depend both on output gap and production unit costs decomposed into labour costs, costs of imported goods approximated by exchange rate and other costs. As regards, the wage equations are built assuming a negotiation process between entrepreneurs, unions and government representatives. It implies that their real level depends on the rate of unemployment and in the long-run on the labour productivity. The financial flows are decomposed into the credits (loans) and deposits. Specific equations explain the incomes and expenditures of the state budget and the financial sector. A submodel explains the balance of payment items.